Model Kolaborasi Stakeholder dalam Penguatan Efektivitas Manajemen Pendidikan: Studi pada Madrasah Aliyah Nurul Islam Tengaran - Wulan Priyanggani; Wella Syamkhotsaa; Nadya Fitri (Al-Mudarris, 2026)
The governance of madrasah education is facing increasing complexity due to demands for management effectiveness, accountability, and digital transformation, while stakeholder collaboration remains partial and insufficiently operational. Previous studies have generally positioned collaboration at a participatory level without formulating a collaborative governance model grounded in Islamic values and adaptive to educational technology. This study aims to formulate a stakeholder collaboration model for strengthening the effectiveness of educational management at MA Nurul Islam Tengaran. The research employed a qualitative method with a case study approach involving 22 informants selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, and then analyzed interactively using source, technique, and time triangulation. The findings reveal that stakeholder collaboration evolved into a strategic collaborative governance instrument through four stages: stakeholder mapping based on power–interest analysis, perception alignment through focus group discussions (FGDs), program-based collaboration activation, and adaptive evaluation within the School Work Plan (RKS) cycle. Islamic principles such as shūrā (consultation), ta‘āwun (cooperation), and amanah (trustworthiness) served as ethical foundations in collaborative governance, while the use of digital communication media supported coordination among stakeholders. This study proposes an Islamic Collaborative Governance Framework that integrates collaborative governance, Islamic values, and digital governance orientation in strengthening madrasah educational management.